2021
DOI: 10.1123/jsr.2020-0371
|View full text |Cite
|
Sign up to set email alerts
|

Altered Central Pain Processing in Patients With Chronic Plantar Heel Pain: A Critically Appraised Topic

Abstract: Clinical Scenario: Plantar heel pain is a common condition frequently associated with persistent symptoms and functional limitations affecting both the athletic and nonathletic populations. Common interventions target impairments at the foot and ankle and local drivers of symptoms. If symptoms are predominantly perpetuated by alterations in central pain processing, addressing peripheral impairments alone may not be sufficient. Clinical Question: Do individuals with chronic plantar heel pain demonstrate signs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
6
1
2
Order By: Relevance
“…Im Gegenteil, bei zu häufiger Anwendung und/oder in zu hoher Dosierung besteht die Gefahr für eine Ruptur der Plantarfaszie und/oder einer Atrophie des kalkanealen Fettpolsters und weiterem Weichteilgewebe. Expert*innen empfehlen daher maximal zwei bis drei Injektionen innerhalb eines Jahres, und zwar nur dann, wenn durch die vorherige Injektion eine Symptomverbesserung erkennbar ist 1 , 2 , 4 , 7 , 15 .…”
Section: Konservative Therapieunclassified
See 1 more Smart Citation
“…Im Gegenteil, bei zu häufiger Anwendung und/oder in zu hoher Dosierung besteht die Gefahr für eine Ruptur der Plantarfaszie und/oder einer Atrophie des kalkanealen Fettpolsters und weiterem Weichteilgewebe. Expert*innen empfehlen daher maximal zwei bis drei Injektionen innerhalb eines Jahres, und zwar nur dann, wenn durch die vorherige Injektion eine Symptomverbesserung erkennbar ist 1 , 2 , 4 , 7 , 15 .…”
Section: Konservative Therapieunclassified
“…Sowohl lokal als auch entfernt von der schmerzhaften Region kann eine Schmerzhypersensitivität auftreten. Zudem können psychosoziale Auffälligkeiten vorliegen, weshalb eine rein mechanische Therapie zur Veränderung der Biomechanik des Fußes in diesem Fall nicht ausreichend wäre 14 , 15 .…”
Section: Zentrale Schmerzverarbeitung Und Psychosoziale Einflüsseunclassified
“…Previous studies have identified several factors involved in a complex matrix behind the potential etiopathogenesis of PHP [ 8 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among these factors, foot-level findings (e.g., limited ankle joint dorsiflexion) [ 8 ], presence of active trigger points (TrPs) [ 12 ], reduced muscle strength and endurance [ 8 ], and psychological factors [ 16 , 17 ] could be involved in PHP in a complex matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, foot-level findings (e.g., limited ankle joint dorsiflexion) [ 8 ], presence of active trigger points (TrPs) [ 12 ], reduced muscle strength and endurance [ 8 ], and psychological factors [ 16 , 17 ] could be involved in PHP in a complex matrix. In addition, emerging evidence also supports the presence of altered central nociceptive pain processing in people with PHP [ 13 , 14 ] related to pressure pain hyperalgesia [ 13 , 15 ]. Supporting these associations, some previous studies have reported different interactions between clinical, psychological, and neurophysiological variables in people with PHP [ 12 , 13 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation